Physical discipline as a normative childhood experience in Singapore - Sudo, Mioko (2023)
Background: The cultural normativeness theory posits that specific parenting behaviors can be interpreted as displays of appropriate parenting in contexts where they are deemed normative. Previous studies suggest high acceptance of physical discipline in Singapore, where strict parenting could be interpreted as care for the child. However, there is a lack of studies on the local prevalence and implications of physical discipline. This study aimed to investigate the prevalence of Singaporean children experiencing parental physical discipline, longitudinal changes in this prevalence, and how exposure to physical discipline relates to children’s evaluation of their parents’ parenting. Methods: Participants were 710 children with parental reports of physical discipline at one or more assessments at ages 4.5, 6, 9, and 11 years in the Growing Up in Singapore Towards healthy Outcomes birth cohort study. Parental reports of physical discipline were obtained using the Parenting Styles and Dimensions Questionnaire or the Alabama Parenting Questionnaire across the four assessments. Child reports of their parents’ care and control were obtained using the Parental Bonding Instrument for Children at the age 9 assessment. Prevalence was specified as being exposed to at least one physical discipline at any frequency. A generalized linear mixed model was performed to examine whether children’s age predicted their exposure to physical discipline. Linear regression analyses were conducted to investigate whether children’s exposure to physical discipline predicted their evaluation of their parents’ parenting. Results: The prevalence of children experiencing at least one physical discipline was above 80% at all ages. There was a decrease in this prevalence from age 4.5 to 11 years (B = − 0.14, SE = 0.01, OR = 0.87, p < 0.001). The more frequent the paternal physical discipline children were exposed to, the more likely they were to report lower levels of care (B = − 1.74, SE = 0.66, p = 0.03) and higher levels of denial of psychological autonomy by fathers (B = 1.05, SE = 0.45, p = 0.04). Maternal physical discipline was not significantly associated with children’s evaluation of their mothers’ parenting (ps ≥ 0.53). Conclusions: Physical discipline was a common experience among our Singaporean sample, consistent with the notion that strict parenting could be regarded as a form of care. However, exposure to physical discipline did not translate to children reporting their parents as caring, with paternal physical discipline being negatively associated with children’s evaluations of paternal care.